RECENT REPORTS ON PYRAZOLE-BASED BIOACTIVE COMPOUNDS AS CANDIDATE FOR ANTICANCER AGENTS - Ardiansah, Bayu (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Pyrazole is a five-membered heterocyclic compound containing two nitrogen atoms. Due to its biological significance, design of novel pyrazole derivatives has become an interesting research area. We report the current progress in the development of anticancer agents containing pyrazole ring covering the time span of the past few years (2013â€“2016). The presence of this nucleus is accompanied with some side chains, functional groups, or in combination with other nucleus such as thiazole, thiourea, glucosamine, naphthalimide, and benzofuran. Several biologically active pyrazoles synthesized by numerous researchers across the world are summarized in this paper.